Application of an Alternative Inorganic Acid Antimicrobial for Controlling Listeria monocytogenes in Frankfurters - Bodie, Aaron R.; Dittoe, Dana K.; Feye, Kristina M.; Knueven, Carl J.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2019)
The prevalence of Listeria monocytogenes under refrigerated conditions is a concern for ready to eat meats like Frankfurters. The purpose of this study was to evaluate the bactericidal effect of potential antimicrobials, Bisulfate of Soda (SBS), Nisin and their combination on L. monocytogenes in frankfurters. Antimicrobial treatment concentrations of SBS and Nisin were indicated by performing minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) test. Results of the MIC indicated the concentrations 0.75 and 1.5% SBS and 0.5,1 and 2% Nisin. Frankfurters were inoculated with L. monocytogenes (initial population: 6.65 log CFU/mL and treated with water, SBS (0.75 and 1.5%) nisin (0.5, 1, and 2%) and combinations (0.75% SBS+0.5% Nisin, 0.75% SBS+1% nisin, 1.5% SBS+1% nisin, and 1.5% SBS+2% nisin). After treatment, frankfurters were removed, rinsed in neutralizing buffer, and plated on Oxford agar. Data were analyzed using One-Way ANOVA, linear contrasts and pairwise comparisons in JMP 14.0. Differences were determined using Tukey’s protected HSD and considered significant when P ≤ 0.05. The treatment 1.5% SBS + 2% nisin exhibited the greatest reduction of L. monocytogenes (2.66 log CFU/mL; P<0.001). Although the effectiveness of both SBS and nisin concentrations were similar when compared to (0.75% SBS- 2.19 log CFU/mL; 1.5% SBS- 2.29 log CFU/mL; .5% nisin- 1.99 log CFU/mL; 1% nisin- 2.47 log CFU/mL; 2% nisin- 2.42 log CFU/mL), there was a linear effect shown by the SBS and nisin treatments compared to the tap water treatment (P < 0.0001; P < 0.0001). The effectiveness of 0.75% SBS compared to other treatments using Pairwise comparisons determined that frankfurters treated with 0.75% SBS and 0.75% SBS+1% nisin resulted in lower L. monocytogenes populations than tap water (TW), whereas 0.75% SBS+0.5% nisin was not different (P < 0.0001). Furthermore, when evaluating the efficacy of 1.5% SBS using Pairwise comparisons, 1.5% SBS, and 1.5% SBS combinations were all significantly different than TW (P < 0.0001). Together, both antimicrobials can reduce Listeria without diminishing the appearance of the frankfurter. The results suggest incorporating SBS and nisin as an alternative antimicrobials for frankfurters can be effective for decreasing L. monocytogenes.